Liver Unidentified Bright Object in a Septic Patient - Daniel Peternac; Michael Andreas Patak; Christoph Gubler (Case Reports in Gastroenterology, 2013)
The typical sonographic appearance of liver hemangiomas is a well-demarcated hyperechoic mass with homogeneous echodensity. Focal liver lesions may change their ultrasound characteristics over time. We present a case of dynamic pattern of liver hemangiomas during a state of systemic inflammation.